Reclamation Obligations for Permit Holders in the Mining Sector - Wartiningsih; Nunuk Nuswardani (Technium Social Sciences Journal, 2023)
The need for mineral materials for human life continues to increase. In order to realize the management of natural resources (mining materials) based on justice and sustainability, permits can be granted to companies. Of course, the issuance of permits includes supervision and law enforcement. One of the obligations of mining companies is to carry out reclamation. The Ministry of Energy and Mineral Resources is optimistic that the enactment of Law Number 3 of 2020 concerning Amendments to Law Number 4 of 2009 concerning Mineral and Coal Mining will be able to encourage more effective fulfillment of ex-mine reclamation obligations. However, in reality, the Mining Advocacy Network (Jatam) noted that in 2020 there were 3,092 mine pits that were not reclaimed in Indonesia. Article 161 B paragraph (1) of Law Number 3 of 2020 concerning Amendments to Law Number 4 of 2009 concerning Minerba determines criminal penalties for companies that do not carry out reclamation. On the other hand, Minister of Energy and Mineral Resources Regulation No. 7 of 2014 concerning Reclamation and Post-mining Implementation in Mineral and Coal Mining Business Activities, allows ex-mining pits to be converted. The problem in this paper is that the 2 (two) provisions seem contradictory. This will be examined from the aspect of the formation of laws and regulations which is the embodiment of the pure legal theory of Hans Kelsen. Using a statutory approach and analyzed qualitatively.